La supervivencia de las palabras - García, María Luisa Romana (Miscelánea Comillas, 2005)
A translator is a sort of practical decision-maker: professional translators must always pick up one of several options, with the choice depending mostly on some key linguistic factors underlying a given word, phrase or text. Applied linguistics is the source we should turn to when making this kind of decisions: we will need to know about linguistic manipulation, sociolinguistics, etymology and neology (word coinage, analogy, borrowing and calque).